COMPARISON OF POLITENESS STRATEGIES AND CULTURAL NORMS IN ANGLO-SAXON AND UZBEK FAMILY DISCOURSE (Scientific journal of the Fergana State University, 2025)
Politeness, while often regarded as a universal concept, is understood and practiced differently across cultures, as demonstrated by numerous cross-cultural studies. Communication styles are shaped by cultural values, which determine the way people interact. This study aims to investigate the perceptions of politeness among the English and Uzbeks and to explore how cultural values influence the nature of interpersonal interactions within the family context in these cultures. Data were collected using a sociocultural questionnaire, a discourse completion test (DCT) administered to 100 English and Uzbek participants, and ethnographic observations. The analysis was conducted through the lens of (im)politeness theory, speech act theory, cross-cultural pragmatics, discourse analysis, identity construction research, and the impact of politeness on communication styles. The findings indicate that Anglo-Saxon culture places high value on privacy, distance, and equality, whereas Uzbek culture emphasizes closeness, respect for age, and status. The results further revealed that parent-child interactions in the Anglo-Saxon context are typically egalitarian, with children treating parents as equals, which reflects the low power distance characteristic of this culture. Conversely, Uzbek culture exhibits marked differences in communicative practices in hierarchical relationships, indicating a higher power distance.